Pathology and Epidemiology of Oxalate Nephrosis in Cheetahs. (November 2017) - Mitchell, Emily P.; Church, Molly E.; Nemser, Sarah M.; Yakes, Betsy Jean; Evans, Eric R.; Reimschuessel, Renate; Lemberger, Karin; Thompson, Peter N.; Terio, Karen A.
To investigate cases of acute oxalate nephrosis without evidence of ethylene glycol exposure, archived data and tissues from cheetahs ( Acinonyx jubatus ) from North America ( n = 297), southern Africa ( n = 257), and France ( n = 40) were evaluated. Renal and gastrointestinal tract lesions were characterized in a subset of animals with ( n = 100) and without ( n = 165) oxalate crystals at death. Crystals were confirmed as calcium oxalate by Raman spectroscopy in 45 of 47 cheetahs tested. Crystals were present in cheetahs from 3.7 months to 15.9 years old. Cheetahs younger than 1.5 years were less likely to have oxalates than older cheetahs ( P = .034), but young cheetahs with oxalates had more oxalate crystals than older cheetahs ( P < .001). Cheetahs with oxalate crystals were more likely to have renal amyloidosis, interstitial nephritis, or colitis and less likely to have glomerular loop thickening or gastritis than those without oxalates. Crystal number was positively associated with renal tubular necrosis ( P ≤ .001), regeneration ( P = .015), and casts ( P ≤ .001) but inversely associated with glomerulosclerosis, renal amyloidosis, and interstitial nephritis. Crystal number was unrelated to the presence or absence of colitis and was lower in southern African than American and European animals ( P = .01). This study found no evidence that coexisting chronic renal disease (amyloidosis, interstitial nephritis, or glomerulosclerosis), veno-occlusive disease, gastritis, or enterocolitis contributed significantly to oxalate nephrosis. Oxalate-related renal disease should be considered as a potential cause of acute renal failure, especially in young captive cheetahs. The role of location, diet, stress, and genetic predisposition in the pathogenesis of oxalate nephrosis in cheetahs warrants further study.